The Restless Spinal Cord in Degenerative Cervical Myelopathy - Hupp, M.; Pfender, N.; Vallotton, K.; Rosner, J.; Friedl, S.; Zipser, C.M.; Sutter, R.; Klarhöfer, M.; Spirig, J.M.; Betz, M.; Schubert, M.; Freund, P.; et al. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: The spinal cord is subject to a periodic, cardiac-related movement, which is increased at the level of a cervical stenosis. Increased oscillations may exert mechanical stress on spinal cord tissue causing intramedullary damage. Motion analysis thus holds promise as a biomarker related to disease progression in degenerative cervical myelopathy. Our aim was characterization of the cervical spinal cord motion in patients with degenerative cervical myelopathy.MATERIALS AND METHODS: Phase-contrast MR imaging data were analyzed in 55 patients (37 men; mean age, 56.2 [SD,12.0] years; 36 multisegmental stenoses) and 18 controls (9 men, P = .368; mean age, 62.2 [SD, 6.5] years; P = .024). Parameters of interest included the displacement and motion pattern. Motion data were pooled on the segmental level for comparison between groups.RESULTS: In patients, mean craniocaudal oscillations were increased manifold at any level of a cervical stenosis (eg, C5 displacement: controls [n = 18], 0.54 [SD, 0.16] mm; patients [n = 29], monosegmental stenosis [n = 10], 1.86 [SD, 0.92] mm; P < .001) and even in segments remote from the level of the stenosis (eg, C2 displacement: controls [n = 18], 0.36 [SD, 0.09] mm; patients [n = 52]; stenosis: C3, n = 21; C4, n = 11; C5, n = 18; C6, n = 2; 0.85 [SD, 0.46] mm; P < .001). Motion at C2 differed with the distance to the next stenotic segment and the number of stenotic segments. The motion pattern in most patients showed continuous spinal cord motion throughout the cardiac cycle.CONCLUSIONS: Patients with degenerative cervical myelopathy show altered spinal cord motion with increased and ongoing oscillations at and also beyond the focal level of stenosis. Phase-contrast MR imaging has promise as a biomarker to reveal mechanical stress to the cord and may be applicable to predict disease progression and the impact of surgical interventions.DCMdegenerative cervical myelopathyECGelectrocardiographyPCMRphase-contrast MR imagingRRR wave-to-R wave interval in the ECG